Genocide in Volhynia and Eastern Galicia 1943–1944 - Paweł Naleźniak (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Ukrainian nationalists tried to de-polonize the South-Eastern Borderlands by means of mass genocide and they achieved this goal to a great extent. That, however, puts them on a par with the criminal regimes of Joseph Stalin and Adolf Hitler. The author of this article describes the genocide of Polish inhabitants in Volhynia and Eastern Galicia committed by the Organisation of Ukrainian Nationalists (Orhanizatsiya Ukrayins’kykh Natsionalistiv, OUN) and the Ukrainian Insurgent Army (Ukrainska Povstanska Armiya, UPA) between 1943 and 1944. These events in European history are not well-known.